2018
DOI: 10.1103/physreva.98.032329
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty relations in the presence of quantum memory for mutually unbiased measurements

Abstract: In [1], uncertainty relations in the presence of quantum memory was formulated for mutually unbiased bases using conditional collision entropy. In this paper, we generalize their results to the mutually unbiased measurements. Our primary result is an equality between the amount of uncertainty for a set of measurements and the amount of entanglement of the measured state, both of which are quantified by the conditional collision entropy. Implications of this equality relation are discussed. We further show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…( ) . It is surprising to find that equation ( 26) is theorem 1 in [35]. Similarly, suppose N = 1 and M = d 2 , the efficiency parameter a for GSIC-POVMs will be obtained, satisfying [43…”
Section: The Uncertainty Relationsmentioning
confidence: 99%
See 3 more Smart Citations
“…( ) . It is surprising to find that equation ( 26) is theorem 1 in [35]. Similarly, suppose N = 1 and M = d 2 , the efficiency parameter a for GSIC-POVMs will be obtained, satisfying [43…”
Section: The Uncertainty Relationsmentioning
confidence: 99%
“…Conveniently, the proof of theorem 2 bears resemblance to theorem 1 of [35], with the exception that equations (11), ( 12), (23), and (24) have been suitably substituted.…”
Section: The Uncertainty Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The last type helped to find new separability conditions for bipartite system [8]. Moreover, it was shown that there is an equality between the amounts of uncertainty for MUMs and entanglement of the measured states quantified by the conditional collision entropy [9]. New separability criteria were given for arbitrary d-dimensional bipartite [10][11][12] and multipartite systems [13,14].…”
Section: Introductionmentioning
confidence: 99%